Genetics, Genomics and Breeding of Sorghum 2014
DOI: 10.1201/b17153-13
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Genetic Control of Biotic Stress Resistance in Sorghum for Applied Breeding

Abstract: Sorghum yield and production stability are constrained by various biotic stresses such as different insects and diseases. The biotic stresses not only reduce the yields but results in poor grain quality thus hampering its marketability and utilization leading to severe economic losses. Development of host plant resistance is one of the cheapest and sustainable methods for managing the insect pests and diseases. Improvement in stress resistance will increase ecological fi tness, reduce pesticide use, and facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Glossy leaves (Agrawal and House, 1982), seedling vigour (Jadhav et al, 1986) and trichomes on the abaxial leaf blade (Maiti and Bidinger, 1979) are reported to be the main factors responsible to shoot fly resistance. To identify sources of resistance to shoot fly, a large number of sorghum germplasm accessions were screened and resistance sources were identified (Kumar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Glossy leaves (Agrawal and House, 1982), seedling vigour (Jadhav et al, 1986) and trichomes on the abaxial leaf blade (Maiti and Bidinger, 1979) are reported to be the main factors responsible to shoot fly resistance. To identify sources of resistance to shoot fly, a large number of sorghum germplasm accessions were screened and resistance sources were identified (Kumar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%